Advanced Glycation End Products as a Predictor of Diabetes Mellitus in Chronic Hepatitis C-Related Cirrhosis - Abdel-Razik, Ahmed; Mousa, Nasser; Zakaria, Sahar; Abdelsalam, Mostafa; Eissa, Mohamed; Abd El-Ghany, Mohammed I.; Hasan, Ahmad S.; Elhelaly, Rania; Elzehery, Rasha; El-Wakeel, Niveen; Eldars, Waleed (Frontiers in Medicine, 2020)
Background & Aims: Advanced glycation end products (AGEs) were found to be involved in the pathogenesis of various disorders. Chronic hepatitis C virus infection is the major cause of liver cirrhosis development and glucose metabolism alteration. We aimed to explore the association of AGEs with the development of diabetes mellitus (DM) in patients with cirrhosis in this study. Methods: Only 144 of the 165 non-diabetic patients with cirrhosis were consecutively included in this prospective cohort pilot study, in addition to 72 healthy control subjects. Clinical data and biochemical parameters including basal insulin secretion and insulin sensitivity indices together with AGEs were evaluated in all participants at baseline and every 1 year thereafter for 2 years. Multivariable Cox regression analysis was used to determine the parameters that could predict the development of DM within this period. Results: DM developed in 14 (10%) patients only. Univariate Cox regression analysis showed that AGEs (P=0.004), Homeostatic Model Assessment-Insulin Resistance (HOMA-IR) (P=0.018), HOMA-β (P=0.015), and age (P=0.012) were associated with DM. After adjusting multiple confounders, the multivariable Cox regression model showed that AGEs, HOMA-IR, and age were the strongest variables associated with DM (all P<0.05). Using the receiver operating characteristic curve, AGEs at a cutoff value of more than 82.4ng/ml, had 99.23% specificity, 100% sensitivity, 0.992 area under the curve (AUC) (all P<0.001) for DM prediction. Conclusion: Our study suggests that AGEs are related to increased incidence of DM, especially in patients with cirrhosis, which is very promising in lowering the risk of DM in these patients.